The Management of Kindergarten Students of Little Koala Montessori Karawaci Tangerang - Andriany, Debby; Soefijanto, Totok Amin; Wahyudi, Mochamad (International Journal of Scientific Research and Management (IJSRM), 2018)
This research aims to analyze the process of management of the students. Research was conducted at the Kindergarten Little Koala Montessori Karawaci Tangerang. Methods used the case study method by using a qualitative approach. The results showed, (1) analyzed the need for class capacity, student and teacher ratios, planned new online learner acceptance, interest and talent search and learner ability through psychological test to explore interest and talent and readiness learning, (2) making and revising the school rules of conduct book applicable to learners and understood by parents, picking up students, and ordering the parent contact book and trying to communicate in it or face-to-face directly outside the teaching hours of teachers with the promise (3) provide counseling services to solve problems in the development of learners, learning difficulties, prepare mental development, and instill confidence, character formation, and the availability of facilities and infrastructure such as books in the central library and mini library, healthy canteen school, computer lab, plant area, pets up a special swimming pool for Little Koala Montessori (4) daily learning reports in daily lesson, weekly study reports aimed at principals, Montessori monthly report cards, and reports from the Education Board and building cooperation with graduates and parents student. Based on the findings, it was concluded that the montessori plus method of effective learning management for learners